2017
DOI: 10.1016/j.jstrokecerebrovasdis.2017.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Development, Validation, and Assessment of an Ischemic Stroke or Transient Ischemic Attack-Specific Prediction Tool for Obstructive Sleep Apnea

Abstract: Background Screening instruments for obstructive sleep apnea (OSA), as used routinely to guide clinicians regarding patient referral for polysomnography (PSG), rely heavily on symptomatology. We sought to develop and validate a cerebrovascular disease-specific OSA prediction model less reliant on symptomatology, and to compare its performance with commonly used screening instruments within a population with ischemic stroke or transient ischemic attack (TIA). Methods Using data on demographic factors, anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…After screening titles and abstracts, 2279 studies were excluded because they did not meet the predetermined inclusion criteria. Of the remaining 17 studies, 8 full-text articles were excluded [20][21][22][23][24][25][26][27] ; the reasons for exclusion are listed in online supplemental table S1. Nine studies met Open access the inclusion criteria and were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, 2279 studies were excluded because they did not meet the predetermined inclusion criteria. Of the remaining 17 studies, 8 full-text articles were excluded [20][21][22][23][24][25][26][27] ; the reasons for exclusion are listed in online supplemental table S1. Nine studies met Open access the inclusion criteria and were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…Second, Frey et al ( 48 ) reported a dissociation between subjective sleepiness and performance during sleep deprivation. Third, recent studies have stressed the limitations of OSA subjective screening instruments when making decisions about a referral for PSG ( 49 ). The present study focused on possible attention deficits caused by putative brain damage associated with OSA because this disorder is related to a significantly increased risk of a transient ischemic attack ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose the baseline characteristics [age (Hokett and Duarte, 2019; Scullin et al, 2019), gender (Spencer, 2008), high blood pressure (Borda et al, 2019; Kumar et al, 2019), high blood lipids (Reijmer et al, 2009; Kruisbrink et al, 2017), diabetes (Margolis et al, 2019; Zhu et al, 2019), being overweight (Mora-Gonzalez et al, 2019; Yeo et al, 2019), atrial fibrillation (Takii et al, 2016; Yeung et al, 2019), smoking (Blaes et al, 2019; Cohen et al, 2019), family history of stroke (Baumann et al, 2012; Reeves et al, 2014), and history of transient ischemic attack (Takahashi et al, 2009; Sico et al, 2017)] according to previous reports indicating that these parameters would affect sleep and memory. The statistical difference for baseline characteristics was insignificant between the two groups (Table 1, p > 0.05).…”
Section: Resultsmentioning
confidence: 99%